2010
DOI: 10.1007/s00228-010-0785-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of CYP2A6 and xanthine oxidase enzyme activities in the Serbian population

Abstract: Purpose The main aim of the study was to investigate the distribution of cytochrome P450 2A6 (CYP2A6) and xanthine oxidase (XO) enzyme activities in the Serbian population. Secondly, we tested the influence of genetics (CYP2A6 polymorphism), sex, and cigarette smoking on both enzymes. Methods One hundred forty healthy Serbian volunteers were genotyped for common CYP2A6 alleles. In 100 of them, CYP2A6 and XO activities were determined by the urinary 17U/17X and 1U/(1U+1X) ratios, respectively, after oral admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 40 publications
3
30
0
1
Order By: Relevance
“…The volume and pH of the urine collected were measured, pH was adjusted to 3.5 with 0.1 M HCl, and 20 mL aliquots were stored at -20°C until analysis. Molar concentrations of caffeine metabolites 17X (1,7-dimethylxanthine or paraxanthine) and 17U (1,7-dimethyluric acid) were determined using high-performance liquid chromatography, and the CYP2A6 enzyme activity was assessed using 17U/17X ratio (Djordjevic et al, 2010;Nowell et al, 2002).…”
Section: Cyp2a6 Phenotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…The volume and pH of the urine collected were measured, pH was adjusted to 3.5 with 0.1 M HCl, and 20 mL aliquots were stored at -20°C until analysis. Molar concentrations of caffeine metabolites 17X (1,7-dimethylxanthine or paraxanthine) and 17U (1,7-dimethyluric acid) were determined using high-performance liquid chromatography, and the CYP2A6 enzyme activity was assessed using 17U/17X ratio (Djordjevic et al, 2010;Nowell et al, 2002).…”
Section: Cyp2a6 Phenotypingmentioning
confidence: 99%
“…Moreover, CYP2A6 enzyme activity appears to be affected by concomitant drug use, including rifampicin, dexamethasone, phenobarbital, and ketokonazole Tomaszewski et al, 2008) CYP2A6 enzyme activity display pronounced inter-ethnic variations between African Americans, Asians, and Caucasians (Djordjevic et al, 2010;Kandel et al, 2007;Nakajima et al, 2006), and CYP2A6 genetic variation is commonly considered as the major cause for the observed differences. Various factors such as ethnicity (Djordjevic et al, 2010(Djordjevic et al, , 2013Kandel et al, 2007;Nakajima et al, 2006), genotype Pitarque et al, 2004), sex (Kandel et al, 2007;Mwenifumbo et al, 2007), age ( Johnstone et al, 2006;Sinues et al, 2008), cigarette smoking (Djordjevic et al, 2010;Mwenifumbo et al, 2007), and oral contraceptive use (Sinues et al, 2008) are reported to influence CYP2A6 enzyme activity. However, such findings are often inconsistent (Begas et al, 2007;Djordjevic et al, 2010;Kadlubar et al, 2009;Mahavorasirikul et al, 2009), warranting further investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2A6*1A is found in almost all populations studied such as Caucasian populations (Spanish, British, French, Swedish and Serbian), which range from 57-67 % (Djordjevic et al, 2010[30], 2013[31]; Gambier et al, 2005[42]; Huang et al, 2005[54]; Nakajima et al, 2006[91], 2004[95]; Oscarson, et al, 1999[102]; Soriano et al, 2011[124]), Africans, and Ethiopians, which reported an allele frequency of 34.8 % (Aklillu et al, 2014[1]). However, in African Americans, Ghanaians and Namibians the frequencies were between 66.5-80.5 % (Gyamfi et al, 2005[45]; Nakajima et al, 2004[95]; Takeshita et al, 2006[129]) while it was the opposite in Asians.…”
Section: Population Distribution Of Cyp2a6 Allelesmentioning
confidence: 99%
“…CYP2A6*1B frequency is higher in East and South Asian populations and is reported as 26.7-54.2 % (Ariyoshi et al, 2002[6]; Djordjevic et al, 2013[31]; Islam et al, 2013[59]; Ito et al, 2015[60]; Iwahashi et al, 2004[61]; Kwon et al, 2001[70]; Lourembam et al, 2015[77]; Mahavorasirikul et al, 2009[79]; Nakajima et al, 2001[92], 2006[91]; Nurfadhlina et al, 2006[98]; Oscarson et al, 1999[102]; Peamkrasatam et al, 2006[107]; Schoedel et al, 2004[117]; Takeshita et al, 2006[129]; Tiwawech et al, 2006[136]; Topcu et al, 2002[137]; Yoshida et al, 2002[150]; Yusof and Gan, 2009[152]). In Caucasians (Nonspecific, North American, Spanish, British, French, Swedish and Serbian) a frequency of 27.6-33.5 % (Bloom et al, 2011[17]; Djordjevic et al, 2013[31], 2010[30]; Gambier et al, 2005[42]; Haberl et al, 2005[46]; Huang et al, 2005[54]; Nakajima et al, 2006[91], 2004[95]; Oscarson et al, 1999[102]; Schoedel et al, 2004[117]; Soriano et al, 2011[124]) is reported, but it is lower in Turkish populations (25.9-26.7 % (Takeshita et al, 2006[129]; von Richter et al, 2004[142])). African populations such as African American, Ghanaian and Namibian show lower frequencies (11.2-19.8 % (Gyamfi et al, 2005[45]; Ho et al, 2009[49]; Mwenifumbo et al, 2008[87]; Nakajima et al, 2006[91], 2004[95]; Schoedel et al, 2004[117]; Takeshita et al, 2006[129])), except for Ethiopian populations (31.3 % (Aklillu et al, 2014[1])).…”
Section: Population Distribution Of Cyp2a6 Allelesmentioning
confidence: 99%